PENGARUH KONTEN KEKINIAN AKUN BERITA DI MEDIA SOSIAL TERHADAP MELEK POLITIK GENERASI MUDA (Studi Deskriptif Followers Twitter @catchmeupid, @narasinewsroom, dan @asumsico) - Rishanti Sharikharani, (2023)
The low political literacy rate of the young generation will result in the young generation being indifferent to the state of politics. The factor that makes young people apathetic and indifferent to politics is that they view politics as bad and boring, which lowers their trust in the political world and has an impact on the young generation's low interest in politics. One of the most popular platforms for social media is Twitter. Current content news accounts on Twitter that are loved by the young generation are @catchmeupid, @narasinewsroom, and @asumsico. This study aims to determine the effect of current content news accounts on social media on the political literacy of the young generation. The theoretical basis used is uses and gratification, this theory argues that the satisfaction of using the media will have an impact on how the media affects the user's life. This research uses descriptive quantitative research with survey methods. The technique uses correlation analysis, regression analysis, coefficient of determination test, and hypothesis testing. The results showed that the correlation between variable X and variable Y had a low but definite relationship. Based on the results of the coefficient of determination test, it is shown that there is an influence of 13.4%. The results of the hypothesis test also show that Ha is accepted, so it can be concluded that there is an influence of the current content of news accounts on social media on the political literacy of the young generation.